2010
DOI: 10.1177/1553350610384406
|View full text |Cite
|
Sign up to set email alerts
|

Single-Access Transumbilical Laparoscopic Nissen Fundoplication Performed With New Curved Reusable Instruments

Abstract: SALN is feasible to be performed with curved reusable instruments, which avoid the conflict between the instruments' tips inside the abdomen or between the surgeon's hands outside. Cost of the procedure remains similar to standard laparoscopy because only reusable material is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
(15 reference statements)
0
12
0
1
Order By: Relevance
“…Publication year ranged from 2010[11] to 2016[14,30]. Although initial references consisted of case reports[11,12,18,23,27,29], subsequent trials included retrospective[14,19-22,24-26,30,31] and prospective[17,32] studies. All eligible trials were performed in a single institution.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Publication year ranged from 2010[11] to 2016[14,30]. Although initial references consisted of case reports[11,12,18,23,27,29], subsequent trials included retrospective[14,19-22,24-26,30,31] and prospective[17,32] studies. All eligible trials were performed in a single institution.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that, in the majority of the included studies (Table 3), a commercial SP device, such as SILS™[11,18-22], Triport Plus™[32], Wrapdisk™[28], X-CONE[19], or EZ Access™[14], was applied, several trials[12,14,19,20,23,25,29,32] reported the introduction of conventional or low profile trocars through a single abdominal incision. In most operations[14,21,22,25,28,30], conventional laparoscopic instruments were used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sus aplicaciones actuales se han extendido a un sinnúmero de procedimientos más complejos como: colectomía [26][27][28][29][30][31] , nefrectomía [32][33][34] , cirugía antirrefl ujo 35,36 , esplenectomía 37,38 , histerectomía 39,40 , hepatectomías 41 , etc. La cirugía bariátrica no ha sido ajena a estos avances, publicándose múltiples exitosas experiencias en banda gástrica ajustable (BGA) [42][43][44] y GM 12,15,16,18 .…”
Section: Discussionunclassified